APPLYING FUZZY LOGIC AND IOT FOR INTELLIGENT AUTOMATION IN CRAYFISH WATER QUALITY CONTROL - Arifin, Miftahol; Laili, Umi; Ansyah, Adi Surya Suwardi (Universitas Trunojoyo Madura, 2024)
Crayfish, known for their high market value due to their substantial meat volume compared to other freshwater shrimp, necessitate improved cultivation efficiency, which can be significantly enhanced with advanced technology. In this study, we designed a highly effective automatic water quality control system specifically for crayfish cultivation that strategically integrates an Internet of Things (IoT)-based control system and a smartphone application. Uniquely, the system incorporates fuzzy logic within the decision-making algorithm, which maintains water quality by adaptively adjusting drainage and temperature control parameters based on dynamic pH and turbidity conditions. This seamless and responsive mechanism ensures optimal cultivation conditions are maintained efficiently. This study manifests that this novel IoT and fuzzy logic technology integration proved effective for automatic water quality control and monitoring. The research contribution is the pioneering integration of fuzzy logic and IoT technologies to devise an intelligent automation system for crayfish water quality control. This system offers real-time remote monitoring and control from a smartphone application and automatically adapts to varying pH and turbidity conditions, ensuring consistently optimal water quality for crayfish cultivation. Such a system holds the potential to set a new standard for precision aquaculture, elevating productivity and sustainability within the crayfish farming sector.